2020
DOI: 10.3390/ani10030417
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use on Italian Pig Farms and its Relationship with Husbandry Practices

Abstract: Simple Summary: Quantifying antimicrobial use (AMU) in livestock using dose-based methods is useful for identifying potential risk factors related to AMU and to promote responsible AMU. Herewith, we investigated the temporal patterns and effects of several structural and management factors on AMU in a sample of pig farms in northern Italy during a period of three years. Overall, AMU showed a large variability between farms and no significantly decreasing trend. However, in several farms, a significant AMU redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
3
19
1
Order By: Relevance
“…We found tetracycline and quinolones being the most used antibiotics due to being cheap, readily available and accessed easily, without restrictions (12,43), and are often sold by informal vendors at informal markets and even along the road (10, 44). Use of tetracycline in animal has been documented in Cameroon and Ghana probably since they are cheaper and has broad-spectrum activity against variety of diseases (34,45,46). The wide spread use of quinolone observed in this study corresponds to the one reported in the previous studies (37,47,48) that quinolones are widely used in animals for diarrhoea treatments and prophylactic despite the fact that they are expensive.…”
Section: Discussionsupporting
confidence: 75%
“…We found tetracycline and quinolones being the most used antibiotics due to being cheap, readily available and accessed easily, without restrictions (12,43), and are often sold by informal vendors at informal markets and even along the road (10, 44). Use of tetracycline in animal has been documented in Cameroon and Ghana probably since they are cheaper and has broad-spectrum activity against variety of diseases (34,45,46). The wide spread use of quinolone observed in this study corresponds to the one reported in the previous studies (37,47,48) that quinolones are widely used in animals for diarrhoea treatments and prophylactic despite the fact that they are expensive.…”
Section: Discussionsupporting
confidence: 75%
“…The choice of which indicator to use should consider stakeholder understanding, relevance to stakeholders, or preference and availability of the input parameters required, such as days at risk. The nDDDvetCA/PCU (4) could be used in datasets or data collection points where the time component is unavailable or constant (e.g., annual aggregated sales data), or in smaller scale targeted studies (32).…”
Section: Discussionmentioning
confidence: 99%
“…These units describe the daily amount of active ingredient required for the treatment of an animal with a standardized weight. Recently, the EMA published guidelines for the development and publication of indicators for the description of antimicrobial use in veterinary medicine, but has also made such indicators available in the form of Defined Daily Doses (DDDvet) and Defined Course Doses (DCDvet) (21). The DDDvet values based on data from nine European countries have been shown in some cases to differ considerably from the dosages specified in the respective national summaries of product characteristics (SPCs).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, national DDDs and DCDs have been developed in several countries (15,22,23). For this reason, separate Defined Daily Doses (DDDch) and Defined Course Doses (DCDch) were developed for Switzerland, some of which consequently showed considerable deviations from the indicators published by the EMA (21,(23)(24)(25)(26). Due to these discrepancies, some authors consider the so-called treatment incidence based on used daily doses, which describes the proportion of treated animals at Abbreviations: AMU, antimicrobial usage; AS, active substance; ATI, Animal Treatment Index; DDDch, Defined Daily Dose Switzerland; DCDch, Defined Course Dose Switzerland; DDDvet, Defined Daily Dose (EMA); DCDvet, Defined Course Dose (EMA); EMA, European Medicines Agency; Min, minimum; Max, maximum; NT, number of treatment days; nDDDch, number of DDDch; SD, standard deviation; SW, standard weight; VMP, Veterinary Medical Product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation